Maternal Blood Group Is a Possible Predictor for Developing Congenital Heart Disease in Turkish Children with Down's Syndrome - Kandur, Yasar; Kocakap, Derya Beyza Sayın; Alpcan, Aysegul; Sanlı, Cihat; Sayan, Cemile Dayangan; Koyuncu, Ömer Lütfi (Journal of Pediatric Genetics, 2023)
We aimed to evaluate the clinical characteristics and the risk factors for the anomalies of Down's syndrome (DS) patients and reviewed the relation of blood groups of the patients and the mothers with these anomalies. Pediatric patients who were diagnosed with trisomy 21 between 2010 and 2022 were enrolled in this study. The medical records of the DS patients and their parents were retrospectively reviewed. A total of 48 patients applied to our clinic. 24 (50%) patients were diagnosed with congenital heart disease. 21 (43.75%) patients had hypothyroidism. The distribution of individual congenital heart defects (CHDs) was as follows: ventricular septal defect in eight (33.3%) patients, one of which also had patent ductus arteriosus (PDA); atrioventricular septal defects in seven (29.1%) patients; atrial septal defects in four (16.6%) patients, one of which also had patent ducus arteriosus; and PDA in five (20.8%) patients. One (4.2%) patient had tetralogy of Fallot. The incidence of CHD in patients with maternal blood group A was significantly higher than those without CHD, with a prevalence of 63.6 and 21.1%, respectively (p = 0.020). Binary logistic regression analysis showed that maternal blood group A was a risk factor for CHDs (odds ratio = 6.563; 95% confidence interval: 1.259–34.204; p = 0.025). Although we found that the rate of advanced father age was high in hypothyroidism type, the regression analysis showed that it was not a risk factor. We found that maternal blood group A increased the likelihood of being born with CHDs in DS.
Keywords: Down's syndrome; congenital heart defects; hypothyroidism; maternal blood group A